Impact of U.S. Market Access on Local Labor Markets in Vietnam - Hoang, Trung X. (World Bank, Washington, DC, 2018)
This paper examines the impact of U.S. market access on local labor markets in a developing country, Vietnam. The study finds that following the implementation of the Vietnam–United States bilateral trade agreement in December 2001, manufacturing employment increased in provinces that were more exposed to U.S. tariff cuts. In those provinces, employment also increased in many service sectors, reflecting strong spillovers of job gains. The new job opportunities have attracted labor from agriculture, thus reducing agricultural employment. The paper examines three possible channels of job gain spillovers, namely, demand, production, and real estate. Although there is evidence for all three channels, the demand channel is the most important.